A Randomized Trial of a Classroom Intervention to Increase Peers' Social Inclusion of Children with Attention-Deficit/Hyperactivity Disorder - Mikami, Amori Yee (2012)
OBJECTIVE: Interventions for peer problems among children with Attention-Deficit/Hyperactivity Disorder (ADHD) typically focus on improving these children's behaviors. This study tested the proposition that an adjunctive component encouraging the peer group to be socially inclusive of children with ADHD would augment the efficacy of traditional interventions. METHOD: Two interventions were compared: Contingency Management Training (COMET), a traditional behavioral management treatment to improve socially competent behavior in children with ADHD, and Making Socially Accepting Inclusive Classrooms (MOSAIC), a novel treatment that supplemented behavioral management for children with ADHD with procedures training peers to be socially inclusive. Children ages 6.8 – 9.8 (24 with ADHD; 113 typically developing [TD]) attended a summer day program grouped into same-age, same-sex classrooms with previously unacquainted peers. Children with ADHD received both COMET and MOSAIC using a repeated measures crossover design. TD children provided sociometric information about the children with ADHD. RESULTS: Whereas the level of behavior problems displayed by children with ADHD did not differ across treatment conditions, children with ADHD displayed improved sociometric preference and more reciprocated friendships, and received more positive messages from peers, when they were in MOSAIC relative to in COMET. However, the beneficial effects of MOSAIC over COMET predominantly occurred for boys relative to girls. CONCLUSIONS: Data support the concept that adjunctive procedures to increase the inclusiveness of the peer group may ameliorate peer problems among children with ADHD, and suggest the potential utility of modifying MOSAIC to be delivered in regular classroom settings.